Capacity building in the use of GEM parboilers - Ahmed, Dembele; Ndindenga, Sali Atanga (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Women were trained in the use of the GEM parboiling technique from 26 to 28 October 2022 in Mali. GEM is an improved parboiling technology that enhances the quality of rice, and was developed to reduce drudgery, the risk of heat burns, and exposure to smoke by operators who are mostly women. Women parboilers who use the GEM technology in Mali made an extra 200 USD on every ton of rice parboiled compared to parboilers using the traditional system. The GEM parboiling technology has a higher output rate of up to 25 tons of milled rice per month of high quality (lighter and uniform color, absence of heat-damaged grains and impurities, low levels of broken fractions). The GEM parboiling technology reduces expenditure on firewood from 1.83 to 0.64 USD per 100kg of paddy parboiled. The GEM parboiling technology reduces the steaming time from about 60-90 min to 20-25 min per 100kg of paddy. The internal rate of return (IRR) of the GEM parboiling technology is 70% compared to 14% for the traditional technology. Finally, the GEM parboiling technique uses rice husk as energy source and reduces CH4 emissions.